2018
DOI: 10.1016/j.jhep.2018.05.021
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal HIF-1α deletion exacerbates alcoholic liver disease by inducing intestinal dysbiosis and barrier dysfunction

Abstract: Alcohol consumption alters gut microbiota and multiple intestinal barrier protecting factors that are regulated by intestinal hypoxia-inducible factor 1α (HIF-1α). Absence of intestinal HIF-1α exacerbates gut leakiness leading to an increased translocation of bacteria and bacterial products to the liver, consequently causing alcoholic liver disease. Intestinal specific upregulation of HIF-1α could be developed as a novel approach for the treatment of alcoholic liver disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
134
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 186 publications
(140 citation statements)
references
References 61 publications
5
134
0
1
Order By: Relevance
“…27 Recently, probiotics have been used as a kind of functional microbes, these have good physiological and biochemical functions for humans, and some researchers have demonstrated that probiotics can effectively attenuate alcoholic liver injury. [32][33][34][35] Forsyth et al, showed the correlation of ALD with oxidative stress and pointed out that LGG could maintain intestinal barrier function by reducing alcohol-oxidative stress and improve the alcoholic fatty liver disease. 36 In previous studies, we demonstrated that…”
Section: Discussionmentioning
confidence: 99%
“…27 Recently, probiotics have been used as a kind of functional microbes, these have good physiological and biochemical functions for humans, and some researchers have demonstrated that probiotics can effectively attenuate alcoholic liver injury. [32][33][34][35] Forsyth et al, showed the correlation of ALD with oxidative stress and pointed out that LGG could maintain intestinal barrier function by reducing alcohol-oxidative stress and improve the alcoholic fatty liver disease. 36 In previous studies, we demonstrated that…”
Section: Discussionmentioning
confidence: 99%
“…Because of the gut-liver circulation via the gut-microbiota-liver axis, nutrients, bacterial products/toxins and metabolites from the gut enters the liver, which play important roles in the progression of liver disease (Wiest et al, 2017). Previous studies indicate that compositional changes of the gut microbiota are closely related to chronic liver diseases, such as non-alcoholic fatty liver disease (NAFLD) (Bibbò et al, 2018;Hoyles et al, 2018;Ponziani et al, 2018), non-alcoholic steatohepatitis (NASH) (Yamada et al, 2017;Bomhof et al, 2018;Ye et al, 2018), alcoholic liver disease (ALD) (Hartmann et al, 2018;Shao et al, 2018;Stärkel et al, 2018), hepatic encephalopathy (HE) (Tilg et al, 2016;Mancini et al, 2018), cirrhosis (Garcia-Tsao and Wiest, 2004;Bajaj et al, 2018a;Guo et al, 2018), hepatocellular carcinoma (HCC) (Zamparelli et al, 2017), and HBV infection. Increasing evidence suggests that the gut microbiota has evolved as a new important player in the pathogenesis of hepatitis B virus-induced chronic liver disease.…”
Section: Introductionmentioning
confidence: 99%
“…Under normal circumstances, translocating pathogens will be endocytosed within the lamina propria and mesenteric lymph nodes ( 33 ). However, if the host mucosal immune system is compromised, these defense mechanisms may fail, thus permitting the evasion and survival of bacteria at distant, extraintestinal sites ( 62 , 63 ). Perturbed gut integrity and permeability may allow pathogens translocate into the circulation, which can increase the host’s susceptibility to various types of diseases by inducing chronic or acute inflammatory responses ( 3 ).…”
Section: Discussionmentioning
confidence: 99%